2017
DOI: 10.1016/s1473-3099(16)30476-5
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines, law, and governance: disconnects in the global control of airline-associated infectious diseases

Abstract: International air travel is increasingly affecting the epidemiology of infectious diseases. A particular public health, economic, and political concern is the role of air travel in bringing infectious passengers or vectors to previously non-endemic areas. Yet, little research has been done to investigate either the infection risks associated with air travel or the empirical evidence for the effectiveness of infection control measures on aircraft and at borders. We briefly review the interface between internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
0
22
2
1
Order By: Relevance
“…The diagnostic capacity and protocols applied in airport controls have been discussed using the experience from SARS [31,32]. Grout et al [33] identified several inconsistencies in infection control measures and major differences in how national and international legislation is enforced by airlines and airports. The differences in the diagnosing quality may affect the number of cases reported.…”
Section: Limitations To Predictive Capacitymentioning
confidence: 99%
“…The diagnostic capacity and protocols applied in airport controls have been discussed using the experience from SARS [31,32]. Grout et al [33] identified several inconsistencies in infection control measures and major differences in how national and international legislation is enforced by airlines and airports. The differences in the diagnosing quality may affect the number of cases reported.…”
Section: Limitations To Predictive Capacitymentioning
confidence: 99%
“…The purpose of this study was to examine the content of the websites for the global commercial passenger airlines within the six major airline conglomerates to determine: a) the extent to which the airline websites contained information about infection control and prevention of infectious diseases, and b) to determine how useful that information was with respect to infection control and the prevention of infectious diseases. More than three billion passengers travel by air annually, with the majority of journeys occurring in less than 24 h [49]. This brings significant challenges for measures to minimise the spread of infectious diseases and to prevent and control infectious diseases outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Air travel has never been easier, cheaper or safer [1]. The speed, accessibility and efficiency of air travel sets it well apart from land and sea travel with respect to the volume and speed at which people travel around the world [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations